Control of labour for one’s own employer within the meaning of Article 8 item 2a of the Social Insurance System Act - Kiełbowicz-Dziwulska, Agnieszka (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
This article presents the principles for performing the control of social contribution payers with regard to work for one’s own employer. The issue concerning work for one’s own employer is regulated in Article 8 item 2a of the Social Insurance System Act. The purpose of this regulation was to protect the rights of insured persons employed on the basis of an employment relationship and a civil law contract, for whom social security contributions may potentially not be paid on the entire income received. The article includes the origins of the legal regulation, the concept of work for one’s own employer and its interpretation. It would seem that the well-established line of court case law clearly indicating the obligation to pay social contributions for an employee performing the work for his own employer under a civil law contract should sufficiently clarify the application principles of this regulation. Therefore, this means that the reason for irregularities in this area may be the search for savings within the range of staff employment costs, which are, amongst other things, social security contributions in addition to salary costs and taxes. However, flexibility in forms of employment can not be used to circumvent the applicable regulations of the law. In this study, the arguments of social security contribution payers against the application of Article 8 item 2a of the Act on the Social Insurance System are presented, as well as the characteristics and subject matter scope of the control in field of work for labour one’s own employer, including the rights of social insurance inspectors to verify the correctness of the fulfillment of social insurance obligations by the payers of social contributions. In the article, the implications and results of a finding of performing work for one’s own employer in terms of the principles for determining the basis for social contributions are discussed. This article also addresses the judicial decisions that have been made in such law cases, as well as the conclusions and proposed solutions emerging in the associated literature.